Governance and food security in an age of globalization - Paarlberg, Robert L. (International Food Policy Research Institute, 2002)
Whose responsibility is it to assure food security in an age of globalization? Is improved governance at the international level our greatest need, or are governance deficits most severe at the national level? When national governments lag in assuring food security for their own citizens, can outsiders help make up the resulting governance deficit? What role can bilateral donors and international financial institutions, such as the World Bank, play? Is it possible for NGOs to step in to do the job? These and related pressing questions are addressed in this discussion paper by Robert Paarlberg. He argues that the problems of hunger and food insecurity urgently require a national, not global focus. Many national governments in developing countries still do not provide essential public goods, such as civil peace, rule of law, transport infrastructure, clean water, electrical power, and public research to generate new agricultural productivity — essential ingredients in the effort to boost incomes. For tackling hunger, the weak per-formance of nation-states remains most critical—and in most critical need of improvement. According to Paarlberg, the governance challenge as far as food security is concerned is to persuade sovereign governments to provide the necessary public goods that would ensure access to adequate food. This paper was commissioned for IFPRI’s 2020 Vision Initiative conference, “Sustainable Food Security for All by 2020,” held on September 4–6, 2001, in Bonn, Germany. A summary version was presented at the session on “Whose Responsibility Is It To End Hunger?” The presentation sparked a long overdue discussion on who are the key actors in the effort to eliminate hunger, how their role has changed over time, and what their responsibilities are likely to be in the future. (from Foreward by Per Pinstrup-Andersen Director General, IFPRI)